O Conselho Municipal de Educação de Sorocaba/SP: a gestão democrática e a busca pela qualidade socialmente referenciada - Almenara, Gilsemara Vasques Rodrigues (Universidade Federal de São Carlos, 2018)
The objective of this research was to analyze the main mechanisms and strategies that guide the democratic management influence starting from the organization and operation of the Municipal Educational Council of Sorocaba/SP (C.M.E.SO) on the perception of its counselors. The methodological path is preliminarily a bibliographic survey on the specialized literature on the subject and through the Bank of CAPES based on the theses and dissertations from 2006 to 2016 amounting to 32 dissertations and 3 PhD theses. A qualitative approach was used, and data collected by means of analyzing the content based on the works of Bardin (1977, 2010, 2011), relative to the records and sayings of the respondents. The procedures used for data collection includes: 1. Script of the Respondent who submitted questions related to personal training and representation in C.M.E.SO; 2. Preliminary Survey Script, which contextualizes the city of Sorocaba/SP and the C.M.E.SO as to your organization and functioning; 3. Semi-structured interview script directed to the municipal education directors held with five advisers having as a criterion of choice of respondents, advisers who participated in the development of PME and that remained on the C.M.E.SO later. The study as a whole made possible to conclude that over the 10 years investigated, the C.M.E.SO sought its autonomy and participation on the municipal education through its normative functions, deliberative and advisory bodies. It’s notable that on the respondent’s speech that the Agency presents sharp dependency of the government, regarding the structural issues, such as: budget to its own actions, physical structure for its operation and targeting guidelines in relevant educational issues. The guiding democratic management axis must still be well worked by the Council, in spite of the increased access that had occurred in the last decade. It is worth noting that a model project of social education has only space by mobilizations and actions of our citizens, albeit represented, that charge and want to understand and act on the contexts and movements of the city’s educational system.
The Municipal Council of education of Sorocaba/SP: democratic management to request for the socially referenced quality
Keywords: Conselhos Municipais de Educação; Qualidade da educação socialmente referenciada; Sorocaba/SP; Escolas - Organização e administração; School management and organization; Quality of education socially referenced; Municipal Council of Education; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL